The parent app understanding families in the digital age - Clark, Lynn Schofield (New York ; Oxford : Oxford University Press, 2013)
New technologies offer new ways for families to connect, access ideas and entertainment, and manage the risks faced by children and teens, but they also bring more responsibilities, choices and challenges. 'The Parent App' explores these differences and provides the kind of guidance backed by thorough research that parents today desperately need.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Internet and families; Internet -- Social aspects; Parent and child